Use of Expedited Partner Therapy for Sexually Transmitted Diseases in College and University Health Centers in the United States, 2011–2012. Issue 10 (October 2015) - Cramer, Ryan; Martinez, Nina; Roberts, Craig; Habel, Melissa A.; Leino, E. Victor; Leichliter, Jami S.
<x xml:space="preserve">Abstract</x> Abstract We examined expedited partner therapy for chlamydia and gonorrhea in college and university health centers by institutional and policy characteristics. Expedited partner therapy awareness and use was low (44.1% used), did not differ by institutional characteristics, and differed by policy environment. Our findings suggest missed opportunities for sexually transmitted disease prevention in college and university health centers.